American Influence on Youth Culture: Representation Analysis on Punk Subculture in Indonesia - Yunia Dewi Fathmawati; Ida Rochani Adi (Rubikon : Journal of Transnational American Studies, 2023)
As globally sprung up, punk subculture is an evidence how American influence has been penetrated in many life facets, including through youth culture. Indonesia becomes one of many countries that accept and practice the subculture. The discussion of punk subculture in Indonesia can reveal the relation between both countries, in which America becomes the powerful party while Indonesia is the submissive ones. To find out American influence in the spread of punk subculture in Indonesia, Representation theory by Stuart Hall is applied in the research. The theory is used in observing punk community both of Indonesia and America in Instagram platforms, particularly some posts that containing of punk elements. By using qualitative method, the result of the research uncovers that Indonesia absorbs American punk elements in two ways: By assimilating it without adding other elements outside of punk and by integrating it to Indonesian context. Both ways show the submissiveness of Indonesia in absorbing the foreign subculture. Yet, especially for the latter, it shows how Indonesia still has a power of resistance in accepting punk subculture by still maintaining mother cultural elements in practicing it, and in the end, it adds a new different color in the global punk scene.